Analisis Manajemen Strategi PT. HM Sampoerna Tbk dengan Pendekatan SWOT, SPACE, BCG, IE Matrix, dan Grand Strategy Matrix - Stefanus Wijaya (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
This study aims to analyze the business strategy of PT HM Sampoerna Tbk. as one of the largest tobacco companies in Indonesia in facing the increasingly complex challenges of the tobacco industry. The analysis was conducted using a strategic management approach through external and internal company analysis. External analysis employed the PESTLE framework and Porter’s Five Forces to identify opportunities and threats arising from political, economic, social, technological, legal, environmental, and industrial competition factors. Meanwhile, internal analysis was conducted to evaluate the company’s management and human resource aspects. This research also utilized several strategic analysis tools, including the IFE Matrix, EFE Matrix, IE Matrix, and BCG Matrix to determine the company’s strategic position. The results indicate that PT. HM Sampoerna Tbk. has a strong internal position with an IFE score of 3.50 and is able to respond effectively to external opportunities and threats with an EFE score of 2.78. Based on the IE Matrix, the company is positioned in the Grow and Build strategy category, while the BCG Matrix analysis shows that Sampoerna’s products are classified as cash cows.